2012
DOI: 10.1155/2012/347875
|View full text |Cite
|
Sign up to set email alerts
|

Conditions of Perfect Imaging in Negative Refraction Materials with Gain

Abstract: Light propagation is analyzed in a negative refraction material (NRM) with gain achieved by pumping. An inherent spatial “walk-off” between the directions of phase propagation and energy transfer is known to exist in lossy NRMs. Here, the analysis is extended to the case where the NRM acts as an active material under various pumping conditions. It is shown that the condition for perfect imaging is only possible for specific wavelengths under special excitation conditions. Under excessive gain, the optical imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Metamaterials, defined as artificial structures not found in nature, possess interesting properties, for example, negative refraction, perfect image, backward-wave radiation, reversals of both Doppler shift and Cherenkov radiation, and so forth [1][2][3][4]. It has recently shown that metamaterials can be used in various areas including microwave and optical components, absorbers, invisible cloaks, and so forth [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials, defined as artificial structures not found in nature, possess interesting properties, for example, negative refraction, perfect image, backward-wave radiation, reversals of both Doppler shift and Cherenkov radiation, and so forth [1][2][3][4]. It has recently shown that metamaterials can be used in various areas including microwave and optical components, absorbers, invisible cloaks, and so forth [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%